2014
DOI: 10.4172/2155-6148.1000394
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Ketamine for Children and Adolescents with Acute Sickle Cell Disease Related Pain: A Single Center Experience

Abstract: Background: Opioids are the mainstay of therapy for painful vasoocclusive episodes (VOEs) in sickle cell disease (SCD). Based on limited studies, low-dose ketamine could be a useful adjuvant analgesic for refractory SCD pain, but its safety and efficacy has not been evaluated in pediatric SCD. Procedure:Using retrospective chart review we recorded and compared characteristics of hospitalizations of 33 children with SCD hospitalized with VOE who were treated with low-dose ketamine and opioid PCA vs. a paired ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…These study results suggest that blockage of the NMDA receptor could reduce tolerance and OIH, and therefore that NMDA antagonists could be useful for pain management associated with SCD [144,145]. Ketamine, used in conjunction with opiates, has been studied in small case studies for the treatment of pain associated with SCD in children, and has shown an acceptable short-term safety profile [146] in addition to the reduction of opioid use and decreased reported pain [147]. Recently a Phase II clinical trial was completed where a low-dose of ketamine in addition to treatment involving opioids was studied for pain stemming for SCD, although no results were provided [148].…”
Section: New Therapeutic Uses Of Known Nmda Receptor Modulatorsmentioning
confidence: 99%
“…These study results suggest that blockage of the NMDA receptor could reduce tolerance and OIH, and therefore that NMDA antagonists could be useful for pain management associated with SCD [144,145]. Ketamine, used in conjunction with opiates, has been studied in small case studies for the treatment of pain associated with SCD in children, and has shown an acceptable short-term safety profile [146] in addition to the reduction of opioid use and decreased reported pain [147]. Recently a Phase II clinical trial was completed where a low-dose of ketamine in addition to treatment involving opioids was studied for pain stemming for SCD, although no results were provided [148].…”
Section: New Therapeutic Uses Of Known Nmda Receptor Modulatorsmentioning
confidence: 99%
“…Further, intraoperative administration of ketamine to patients with chronic back pain and opioid dependence decreases opioid requirements and reduces the incidence of late postoperative pain after spinal fusion (17). Therefore, given the reported analgesic and opioid-sparing effects in acute and chronic pain as well as a favorable safety profile, researchers have argued that ketamine might have a role in modulating SCD pain (18,19).…”
mentioning
confidence: 99%
“…Several groups have reported the use of intravenous (18,(20)(21)(22) and intranasal ketamine (23) in SCD patients presenting with VOEs. Here, we conducted an exploratory study on a large cohort of SCD patients who during admissions for VOEs were treated with subanesthetic doses of ketamine.…”
mentioning
confidence: 99%
“…For the purpose of this report, we defined high‐dose opioid as those exceeding 2 mg/kg/day of oral morphine equivalent. This definition is based on a study indicating that patients requiring those doses of opioid were often treated with ketamine . For this investigation, we examined patient demographics, SCD genotype, analgesic therapy, self‐reported pain scores (numeric rating scale 0 to 10), and treatment‐related hemodynamic changes requiring intervention.…”
Section: Methodsmentioning
confidence: 99%